Controle da emissão visível de nanopartículas baseadas em óxido de zinco - Curcio, Ana Laura (2021)
We present a study of the synthesis processes and of the structural, vibrational and optical properties of Zn1-xCdxO nanostructured system. The Zn1-xCdxO samples were synthesized using mechanosynthesis method, in the compositional range 0 ≤ x ≤ 0.01 and through the microwave assisted solvothermal method with 0 ≤ x ≤ 0.05. These dopant concentrations were chosen with the aim of preserving the crystallographic structure of the matrix and, consequently, all the physical properties related to the structure. Since the modifications induced by doping in these proportions are difficult to be investigated using conventional r-ray diffraction experiments, the development of an alternative method based on Raman spectroscopy that was needed. Such method has proved to be very sensitive in identifying to structural modifications in ZnO systems with dimensions in nanometer scale. The samples produced by mechanosynthesis presented the visible emission being composed of five associated spectral contributions. The developed synthesis method enables the control of the relative intensity of these contributions, which provides the possibility to strongly adjust the visible emission, producing displacements in its maximums up to 80 nm. Due to the large surface-to-volume ratio and the possibility of controlling the morphology, the particles produced by mechanosynthesis allowed us to establish the limit in which the visible photoluminescent emission is dominated by internal point defects, whose density is controlled through doping, or ruled by surface effects. This opens the possibility of an additional control of this emission through adjustments to the synthesis parameters. The analysis of samples produced by solvothermal technique showed that the long-range order decreases as the dopant proportion is increased and that these structural effects are the possible agents of the changes in the gap energy, since this phenomenon may be linked to the decrease in the electronic mobility in disordered structures. The comparison of the Raman spectra of the doped samples indicates that the system produced by solvothermal synthesis presents a stronger quantum confinement, while the system produced by mechanosynthesis has a higher density of electronic states associated with point defects. The use of different parameters adopted in the synthesis processes is an efficient way for the selective control of the emission spectra of ZnO-based nanoparticles in both synthesis mechanisms, allowing the selective modulation of optical emissions, preserving the long-range order of the crystalline structure.